Antibacterial properties of Ag–TiO2 composite sol–gel coatings. Issue 73 (9th August 2015) - Albert, E.; Albouy, P. A.; Ayral, A.; Basa, P.; Csík, G.; Nagy, N.; Roualdès, S.; Rouessac, V.; Sáfrán, G.; Suhajda, Á.; Zolnai, Z.; Hórvölgyi, Z.
<x xml:space="preserve">Abstract</x> This study reveals the connection between the silver-doping method, the resulting nature and amount of the silver dopant together with the structural properties and the long-term antibacterial activity of composite coatings.